The Ethiopian Civil Society Organizations Law and its Role for Social Movement in Ethiopia - Brook Kebede Abebe (Advanced Studies on Socio-Economy Development, 2022)
Civil society organizations (hereinafter called CSOs) are separate entities from the government organizational structure, and they are formed by people who have common needs, interests and values. They are important for organizing social movements at the local and/or international levels. CSOs in Ethiopia have existed as informal community-based organizations and self-help associations. However, formal civil society organization has started to exist with a legal personality recently. In Ethiopia, for a decade and more, as a result of the adoption of the 2009 repressive CSO law, civil society organizations did not entirely take part in their role in the country’s social movements and in the promotion and protection of human rights. However, the said law on several occasions has faced strong criticism from national and international CSOs. Accordingly, recently, in January 2019 the Ethiopian Government amended the preexisting law and enacted a new proclamation, Proclamation 1113/2019. Thus, this paper focuses on the newly promulgated CSO legislation and its role for social movements in Ethiopia, as there are changes made in the system of the CSOs and their activities. Therefore, the paper basically examines the peculiarities of the new Ethiopian CSO law in relation with its role for social movement in Ethiopia. By assessing the positive and the down sides of the new CSO legislation, it investigates the possible contribution of the new Proclamation. It also critically scrutinizes the role of the new CSO law in accelerating and promoting the social movements in Ethiopia. Keywords: Civil Society, CSO, Social Movement, New Proclamation, Ethiopia, NGO.